Ethanol Extract of Ampelopsis brevipedunculata Rhizomes Suppresses IgE-Mediated Mast Cell Activation and Anaphylaxis - Ji-Yeong Park; Min-Jong Kim; Young-Ae Choi; Seung Woong Lee; Soyoung Lee; Yong Hyun Jang; Sang-Hyun Kim (Advances in Pharmacological and Pharmaceutical Sciences, 2024)
More than 20% of the world’s population suffers from allergic diseases, including allergic asthma, rhinitis, and atopic dermatitis that severely reduce the patient’s quality of life. The treatment of allergy has been developed, but there are still unmet needs. Ampelopsis brevipedunculata (Maxim.) Trautv. is a traditional medicinal herb with beneficial bioactivities, such as antioxidant, anti-hypertension, anti-viral, anti-mutagenic, and skin and liver (anti-hepatotoxic) protective actions. However, its anti-allergic effect has not been addressed. This study designed to investigate the pharmacological effect of an ethanol extract of A. brevipedunculata rhizomes (ABE) on mast cell and anaphylaxis models. For in vivo studies, we used ovalbumin-induced active systemic anaphylaxis (ASA) and immunoglobulin (Ig) E-mediated passive cutaneous anaphylaxis (PCA) models. In ASA model, oral administration of ABE (1, 10, and 100 mg/kg) attenuated the anaphylactic responses, such as hypothermia, serum histamine, and IgE productions. In PCA model, ABE also suppressed the plasma extravasation and swelling. The underlying mechanisms of action were identified in various mast cell types. In vitro, ABE (10, 30, and 60 µg/mL) inhibited the release of essential allergic mediators, such as histamine and β-hexosaminidase, in a concentration-dependent manner. ABE prevented the rapid increase in intracellular calcium levels induced by the DNP-HSA challenge. In addition, ABE downregulated the tumor necrosis factor-α and interleukin-4 by suppressing the activation of nuclear factor-κB. Collectively, this study is the first to identify the anti-allergic effect of ABE, suggesting that ABE is a promising candidate for treating allergic diseases.